Introduction: Transformation of nationalism and diaspora in the digital age. Issue 2 (23rd December 2020) - Yusupova, Guzel; Rutland, Peter
Abstract: This introduction to the four papers that make up this themed section locates them in the wider theoretical perspective from which they originate, and highlights the importance of taking into account digital media and technologies as an independent factor that significantly transforms contemporary nationalisms and social identities. Digital media has intensified and accelerated the relationship between culture and politics. It offers new ways of community‐building and identity‐making: both top‐down and bottom‐up, both within the nation‐state and beyond its borders. New research will hopefully explore the complex ways in which both elite and lay understanding and practice of nationalism are evolving in competition and collaboration with each other.